Evaluation of Excess Thermodynamic Parameters in a Binary Liquid Mixture (Cyclohexane + O-Xylene) at Different Temperatures - K. Narendra; P. Narayanamurthy; CH. Srinivasu (E-Journal of Chemistry)
The ultrasonic velocity, density and viscosity in binary liquid mixture cyclohexane with o-xylene have been determined at different temperatures from 303.15 to 318.15 K over the whole composition range. The data have been utilized to estimate the excess adiabatic compressibility (βE), excess volumes (VE), excess intermolecular free length (LfE), excess internal pressure (πE) and excess enthalpy (HE) at the above temperatures. The excess values have been found to be useful in estimating the strength of the interactions in the liquid mixtures. Analysis of these parameters indicates that there are weak interactions among the components of the binary mixtures.